2005
DOI: 10.1590/s1679-62252005000200010
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of juvenile pirarucu (Arapaima gigas, Arapaimidae) in their natural environment, lago Quatro Bocas, Araguaiana-MT, Brazil

Abstract: The stomach content of samples of juvenile Arapaima gigas was analized to obtain information about feeding in natural environments. This species occurs in the Amazonian basin, predominantly in floodplain environment. This is the case of the valley of the middle rio Araguaia, where the lago Quatro Bocas is situated. Juveniles A. gigas prefered insects, microcrustaceans and gastropods, most of autochthonous origin. All the stomachs examined contained at least one food item.
Analisou-se no presente estudo, o c…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 4 publications
3
12
1
1
Order By: Relevance
“…Despite the relatively low sample size in our study, there were significant differences between the size (age) classes studied, with adult arapaima utilising a broader range of prey resources than juveniles (Figures and ). These findings contrast with previous research that has indicated that among immature arapaima the diversity of food decreased with size (Queiroz, ) and that smaller juveniles displayed the greatest trophic plasticity (De Oliveira, Poleto, & Venere, ). Our results indicated that juvenile arapaima feed mainly on prey from lower trophic levels, while adults are able to feed across the entire trophic spectrum.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the relatively low sample size in our study, there were significant differences between the size (age) classes studied, with adult arapaima utilising a broader range of prey resources than juveniles (Figures and ). These findings contrast with previous research that has indicated that among immature arapaima the diversity of food decreased with size (Queiroz, ) and that smaller juveniles displayed the greatest trophic plasticity (De Oliveira, Poleto, & Venere, ). Our results indicated that juvenile arapaima feed mainly on prey from lower trophic levels, while adults are able to feed across the entire trophic spectrum.…”
Section: Discussioncontrasting
confidence: 99%
“…The relatively high number of closely-spaced gill rakers in Arapaima is another indicator of a varied diet, including relatively smaller-bodied prey. Juvenile Arapaima (22-26.5 cm standard length) from the Araguaia River basin of southern Brazil were observed to feed on a variety of invertebrates together with about 53% by volume of detritus (de Oliveira et al, 2005), and ingesting such fine particles would be difficult with widely-spaced gill rakers. Pinese (1996) also concluded that functional morphology of Arapaima feeding structures was more consistent with that of an omnivore than a piscivore.…”
Section: Discussionmentioning
confidence: 99%
“…Arapaima are sometimes characterized as 'predators' (e.g., Forsberg et al, 1993) or 'top predators' in food webs, but some diet studies in Brazil (Queiroz, 2000;de Oliveira et al, 2005) suggest that the characterization of Arapaima as a top predator may be an overly simplistic assumption. Information on sources of energy assimilated by Arapaima can contribute to an understanding of their role in the ecosystem and may have implications for estimating carrying capacity of various habitats for Arapaima populations.…”
mentioning
confidence: 99%
“…The most likely hypothesis to explain these variable mortalities is that feeding of fry depends greatly on the productivity of ponds. As juveniles and fingerlings feeding in the wild consists mainly of zooplankton, insects, insect larvae and small gastropods (Oliveira, Poleto & Venere 2005), the main causes of mortality are probably an insufficient food availability. This hypothesis needs to be tested by a detailed study of the limnological parameters and plankton productivity in the different farming environments.…”
Section: Discussionmentioning
confidence: 99%